TRANSFORMATIONAL LEADERSHIP, CONSERVATION, AND CREATIVITY: EVIDENCE FROM KOREA. (Academy of Management Journal, 2003)
Using a sample of 290 employees and their supervisors from 46 Korean companies, we found that (1) transformational leadership was positively related to follower creativity, (2) followers' “conserva...